Preparation method of high-elasticity optical cable
The high elastic sheath material made of modified spiral carbon nanotubes and modified styrene-butadiene-styrene block copolymer wraps the optical cable core material, solving the aging problem of existing optical cables in special environments, significantly improving the anti-aging performance and tensile fracture resistance of the optical cable.
Patent Information
- Application Number
- CN202411790965.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-12
- Publication Date
- 2025-04-11
AI Technical Summary
The aging problem of existing optical cables is more prominent in special environments, and there is still room for improvement in performance on the market, especially in the absence of anti-aging performance under conditions such as humidity, heat, temperature change, ultraviolet and ozone.
A highly elastic sheathed material made of modified spiral carbon nanotubes, modified styrene-butadiene-styrene block copolymer and polyethylene is wrapped on the optical cable core and made into a highly elastic optical cable through roll pressing. The sheath material is catalytically deposited by nano-ferrous oxide to produce spiral carbon nanotubes, and is modified by nitric acid treatment and sulfoxide chloride reaction to enhance its thermal conductivity and cross-linking properties. At the same time, the anti-aging performance of the optical cable under ultraviolet and ozone conditions is improved by the reaction of the fluorescent complex solution and the premodified styrene-butadiene-styrene block copolymer.
It improves the anti-aging performance and tensile fracture resistance of high-elastic optical cables under humid heat, temperature change, ultraviolet and ozone conditions, and extends the service life of optical cables.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sheath materials, and in particular to a method for preparing a high-elastic optical cable. Background Art
[0002] Optical cable is a cable structure entity made of a single optical fiber, multiple optical fibers or optical fiber bundles plus an outer sheath, which meets the requirements of optical properties, mechanical properties and environmental performance indicators, and is used to realize a communication line for optical signal transmission. The structure of a general optical cable can be divided into optical fiber buffer layer, cable core, tension resistance layer, coating and waterproof layer. According to its structure, it can be roughly divided into ribbon optical cable, all-dielectric self-supporting optical cable, ground wire composite optical cable, submarine optical cable, etc.
[0003] With the development of society and the construction of global integration, optical cables have begun to be laid in various regions, such as the seabed, mountains, forests, deserts and other special environments. Because of constant maintenance, the requirements for the sheath materials of optical cables are getting higher and higher. The market demand for optical cables with corrosion resistance, earthquake resistance, anti-aging and other properties is increasing. However, there are still many areas worth improving in performance on the market. Most of the aged optical cables on the market are anti-ultraviolet aging. The high-elastic optical cable prepared by the present invention has anti-aging properties in a variety of environments. Summary of the invention
[0004] The object of the present invention is to provide a high elastic optical cable and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a high-elastic optical cable is characterized in that the high-elastic optical cable is made of a sheath material made of modified helical carbon nanotubes, modified styrene-butadiene-styrene block copolymer and polyethylene, and the sheath material is wrapped on an optical cable core material and rolled.
[0006] As an optimization, the modified helical carbon nanotubes are prepared by vapor deposition of carbon source gas under the catalysis of nano-iron oxide, and the helical carbon nanotubes are treated with nitric acid and then reacted with thionyl chloride and aminopropyltrimethoxysilane to obtain the helical carbon nanotubes.
[0007] As an optimization, the modified styrene-butadiene-styrene block copolymer is prepared by reacting styrene-butadiene-styrene block copolymer with ethyldiallylsilane, diethoxysilane and p-aminostyrene to obtain a pre-modified styrene-butadiene-styrene block copolymer, and then reacting the pre-modified styrene-butadiene-styrene block copolymer with a fluorescent complex solution.
[0008] As an optimization, the fluorescent complex solution is prepared by reacting 3-furoic acid, 2-mercaptobenzimidazole and neodymium chloride in an ethanol solution.
[0009] As an optimization, the method for preparing the highly elastic optical cable includes the following preparation steps: (1) Treating the helical carbon nanotubes with acid, mixing the acid-treated helical carbon nanotubes, thionyl chloride and tetrahydrofuran in a mass ratio of 1:4:4~1:6:6, stirring and reacting at 40~50°C and 400~500r / min for 2~3h, heating to 60~70°C and continuing stirring and reacting for 2~3h, filtering, standing at 10~30°C and 1~2kPa for 4~6h, and then mixing with aminopropyltrimethoxysilane, triethylamine and dichloromethane in a mass ratio of 3:2:0.5:20~3:3:1:25, stirring at 0~5°C and 300~500r / min for 50~60min, standing at room temperature for 20~24h, filtering and washing with anhydrous ethanol for 3~5 times, and drying at -10~-1°C and 1~10Pa for 6~8h to obtain modified helical carbon nanotubes; (2) Pre-modified styrene-butadiene-styrene block copolymer, fluorescent complex solution and n-hexane are mixed uniformly in a mass ratio of 1:5:3~1:7:5, and then 0.01~0.03 times the mass of pre-modified styrene-butadiene-styrene block copolymer is added with carbodiimide, and the mixture is stirred at 20~30°C and 800~1000r / min for 2~3h, and allowed to stand at 30~40°C and 1~2kPa for 8~10h, filtered and washed with pure water for 3~5 times, and dried at -10~-1°C and 1~10Pa for 6~8h to obtain modified styrene-butadiene-styrene block copolymer; (3) placing the modified helical carbon nanotube in pure water for 2 to 3 minutes, drying it at -10 to -1°C and 1 to 10 Pa for 6 to 8 hours to obtain pretreated modified helical carbon nanotubes; uniformly mixing the pretreated modified helical carbon nanotubes, modified styrene-butadiene-styrene block copolymer, and polyethylene in a mass ratio of 1:1:2 to 1:2:3, kneading at 120 to 140°C for 20 to 30 minutes to obtain a sheath material with a thickness of 3 to 5 mm, wrapping the sheath material on the optical cable core material, and rolling it at 120 to 130°C and 8 to 10 MPa at a speed of 220 to 240 m / min for 2 to 3 times to obtain a high elastic optical cable.
[0010] As an optimization, the preparation method of the spiral carbon nanotubes in step (1) is as follows: acetone, pyridine and acetylene are uniformly mixed in a mass ratio of 1:1:1 to 1:2:3 as a carbon source gas, a glass plate carrier uniformly distributed with nano-iron oxide is placed in a reaction chamber in a nitrogen atmosphere, a carbon source gas 1000 to 1200 times the mass of the nano-iron oxide is introduced at a flow rate of 800 to 1000 sscm at 700 to 800° C., and then aeration is stopped for 5 to 10 minutes, and nitrogen is then introduced at the same flow rate for 10 to 20 minutes, cooled to 10 to 30° C., the product on the glass plate carrier is placed in a hydrochloric acid solution with a mass fraction of 10 to 15%, ultrasonicated at 30 to 40 kHz for 15 to 20 minutes, filtered and washed with anhydrous ethanol and pure water for 3 to 5 times respectively, and dried at -10 to -1° C. and 1 to 10 Pa for 6 to 8 hours to prepare the spiral carbon nanotubes.
[0011] As an optimization, the acid treatment method in step (1) is: the helical carbon nanotubes and 40-50% by mass nitric acid are uniformly mixed in a mass ratio of 1:8-1:10, stirred at 80-90°C and 800-1000 r / min for 20-30 min, filtered after cooling to room temperature, washed with pure water for 3-5 times, and dried at -10--1°C and 1-10 Pa for 6-8 h.
[0012] As an optimization, the preparation method of the pre-modified styrene-butadiene-styrene block copolymer in step (2) is: styrene-butadiene-styrene block copolymer, ethyl diallyl silane and n-hexane are uniformly mixed in a mass ratio of 1:1:8 to 1:1:10, and then 0.03 to 0.05 of the mass of divinyltetramethyldisiloxane platinum salt of styrene-butadiene-styrene block copolymer is added, and the mixture is stirred and refluxed at 70 to 80°C and 500 to 800 r / min for 3 to 4 hours. 5h, add diethoxysilane in an amount of 1.3~1.5 times the mass of styrene-butadiene-styrene block copolymer, continue stirring and reflux for 3~5h, add p-aminostyrene in an amount of 1.3~1.5 times the mass of styrene-butadiene-styrene block copolymer, continue stirring and reflux for 3~5h, let stand at 20~30℃, 1~2kPa for 3~4h, filter and wash with pure water for 3~5 times, and dry at -10~-1℃, 1~10Pa for 6~8h to prepare.
[0013] As an optimization, the preparation method of the fluorescent complex solution in step (2) is: 3-furoic acid, 2-mercaptobenzimidazole, anhydrous ethanol and pure water are mixed evenly in a mass ratio of 1:1:4:4~1:1:6:6, and then 0.3~0.5 times the mass of neodymium chloride of 3-furoic acid is added, and stirred at 30~40°C and 800~1000r / min for 4~5h to prepare the solution.
[0014] As an optimization, the optical cable core material in step (3) is a central tube optical cable, model GYXTS.
[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the high elastic optical cable, the invention prepares the sheath material by using the modified helical carbon nanotube, the modified styrene-butadiene-styrene block copolymer and polyethylene, and wraps the sheath material on the optical cable core material and rolls it to obtain the high elastic optical cable.
[0016] Firstly, carbon source gas is vapor-deposited under the catalysis of nano-iron oxide to obtain spiral carbon nanotubes, and the spiral carbon nanotubes are treated with nitric acid and then reacted with thionyl chloride and aminopropyltrimethoxysilane to obtain modified spiral carbon nanotubes. The spiral structure enables the spiral carbon nanotubes to have more contact with the remaining components of the overall material, has a greater conduction effect on the thermal motion of molecules, improves the overall heat dissipation effect of the material, and thus improves the anti-aging performance of the high-elasticity optical cable under wet heat and temperature change conditions; aminopropyltrimethoxysilane forms an amide bond connection with the spiral carbon nanotubes, and the trimethoxysilane on the modified spiral carbon nanotubes can be decomposed into silanol groups, which are cross-linked with each other through the silanol groups to form a spiral carbon nanotube heat conduction network, thereby improving the overall cross-linking degree while improving the thermal conductivity and thermal stability, thereby improving the anti-aging performance and tensile fracture resistance of the high-elasticity optical cable under wet heat and temperature change conditions.
[0017] Secondly, 3-furoic acid, 2-mercaptobenzimidazole and neodymium chloride are reacted in an ethanol solution to obtain a fluorescent complex solution, styrene-butadiene-styrene block copolymer is reacted with ethyldiallylsilane, diethoxysilane and p-aminostyrene to obtain a pre-modified styrene-butadiene-styrene block copolymer, and the pre-modified styrene-butadiene-styrene block copolymer is reacted with the fluorescent complex solution to obtain a modified styrene-butadiene-styrene block copolymer. The fluorescent complex can absorb strong light and ultraviolet rays and convert them into weak light and heat, thereby reducing the damage of strong light and ultraviolet rays to the material. In an ozone environment, when the whole contains oxidizing substances, the benzimidazole on the fluorescent complex can respond in time, and the metal-sulfur coordination bond is broken to form a benzimidazole containing sulfur free, which reacts with the oxidizing substances. The combination of the fluorescent complex and the pre-modified styrene-butadiene-styrene block copolymer reduces the oxidative decomposition of the main material, thereby improving the anti-aging performance of the high-elasticity optical cable under ultraviolet and ozone conditions; the fluorescent complex and the pre-modified styrene-butadiene-styrene block copolymer form amide bonds that can form hydrogen bonds with the amide bonds on the modified helical carbon nanotubes, so that the fluorescent complex is close to the modified helical carbon nanotubes, and the heat converted by ultraviolet absorption is transferred in time, and the fluorescent complex is protected to avoid loss, which further improves the anti-aging performance of the high-elasticity optical cable under ultraviolet and ozone conditions. At the same time, the silicone chain segments generated during the pre-modification of the styrene-butadiene-styrene block copolymer increase the stability of the styrene-butadiene-styrene block copolymer, reduce the impact of temperature changes on the overall performance, and improve the anti-aging performance of the high-elasticity optical cable under temperature change conditions. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0019] In order to more clearly illustrate the method provided by the present invention, the following embodiments are used to describe in detail the various index testing methods of the high elastic optical cable prepared in the following embodiments. Tensile fracture resistance: The high elastic optical cables obtained in each embodiment and the comparative example materials were taken with the same mass, and the tensile strength was tested and recorded according to GB / T528 standard.
[0020] Anti-aging performance: The high elastic optical cables obtained in each embodiment and the comparative material are taken with the same mass, placed in the same constant temperature aging box, and subjected to aging tests in different environments such as humidity, temperature change, ultraviolet light, and ozone under the same conditions. The tensile strength is measured again after the same period of time, and the performance retention rate is recorded as tensile strength after aging test / initial tensile strength.
[0021] Example 1 A method for preparing a high elastic optical cable, the method for preparing the high elastic optical cable mainly comprises the following preparation steps: (1) Acetone, pyridine and acetylene were mixed in a mass ratio of 1:1:1 as a carbon source gas. A glass plate carrier evenly distributed with nano-iron oxide was placed in a reaction chamber in a nitrogen atmosphere. A carbon source gas 1000 times the mass of nano-iron oxide was introduced at a flow rate of 800 sscm at 700°C, and then the ventilation was stopped for 5 minutes. Nitrogen was then introduced at the same flow rate for 10 minutes. The product on the glass plate carrier was placed in a 10% hydrochloric acid solution, ultrasonicated at 30kHz for 15 minutes, filtered and washed with anhydrous ethanol and pure water for 3 times each, and dried at -10°C and 1Pa for 8 hours to obtain helical carbon nanotubes. The helical carbon nanotubes and 40% nitric acid were mixed in a mass ratio of 1:8, and heated at 80°C and 800r / m in stirring reaction for 30 minutes, cooling to room temperature and filtering, washing with pure water for 3 times, drying at -10°C, 1Pa for 8 hours, and obtaining acid-treated spiral carbon nanotubes; mixing the acid-treated spiral carbon nanotubes, thionyl chloride, and tetrahydrofuran in a mass ratio of 1:4:4, stirring reaction at 40°C, 400r / min for 3 hours, heating to 60°C and continuing stirring reaction for 3 hours, filtering, standing at 10°C, 1kPa for 6 hours, and then mixing with aminopropyltrimethoxysilane, triethylamine, and dichloromethane in a mass ratio of 3:2:0.5:20, stirring at 0°C, 300r / min for 60 minutes, standing at room temperature for 20 hours, filtering and washing with anhydrous ethanol for 5 times, and drying at -10°C, 1Pa for 8 hours to obtain modified spiral carbon nanotubes; (2) 3-furoic acid, 2-mercaptobenzimidazole, anhydrous ethanol and pure water were mixed in a mass ratio of 1:1:4:4, and then 0.3 times the mass of neodymium chloride of 3-furoic acid was added, and the mixture was stirred at 30°C and 800 r / min for 5 h to obtain a fluorescent complex solution; styrene-butadiene-styrene block copolymer, ethyl diallyl silane and n-hexane were mixed in a mass ratio of 1:1:8, and then 0.03 times the mass of divinyltetramethyldisiloxane platinum salt of styrene-butadiene-styrene block copolymer was added, and the mixture was stirred and refluxed at 70°C and 500 r / min for 5 h, and then 1.3 times the mass of diethoxysilane of styrene-butadiene-styrene block copolymer was added, and the stirring and reflux was continued for 3 h, and then styrene-butadiene-styrene block copolymer was added. 1.3 times the mass of p-aminostyrene is continued, stirring and refluxing are continued for 5 hours, standing at 20°C, 1kPa for 4 hours, filtered and washed with pure water for 3 times, and dried at -10°C, 1Pa for 8 hours to obtain a pre-modified styrene-butadiene-styrene block copolymer; the pre-modified styrene-butadiene-styrene block copolymer, the fluorescent complex solution, and n-hexane are mixed uniformly at a mass ratio of 1:5:3, and then 0.01 times the mass of the pre-modified styrene-butadiene-styrene block copolymer is added with carbodiimide, stirred at 20°C, 800r / min for 2 hours, standing at 30°C, 1kPa for 10 hours, filtered and washed with pure water for 3 times, and dried at -10°C, 1Pa for 8 hours to obtain a modified styrene-butadiene-styrene block copolymer; (3) The modified helical carbon nanotubes were placed in pure water for 2 minutes, and dried at -10°C and 1 Pa for 8 hours to obtain pretreated modified helical carbon nanotubes; the pretreated modified helical carbon nanotubes, modified styrene-butadiene-styrene block copolymer, and polyethylene were uniformly mixed in a mass ratio of 1:1:2, and kneaded at 120°C for 20 minutes to prepare a sheath material with a thickness of 4 mm; the sheath material was wrapped on the optical cable core material, and rolled twice at 120°C and 8 MPa at 220 m / min to obtain a high elastic optical cable.
[0022] Example 2 A method for preparing a high elastic optical cable, the method for preparing the high elastic optical cable mainly comprises the following preparation steps: (1) Acetone, pyridine and acetylene were mixed in a mass ratio of 1:1:2 as a carbon source gas. A glass plate carrier evenly distributed with nano-iron oxide was placed in a reaction chamber in a nitrogen atmosphere. A carbon source gas 1100 times the mass of nano-iron oxide was introduced at a flow rate of 900 sscm at 750°C, and then the ventilation was stopped for 7 minutes. Nitrogen was then introduced at the same flow rate for 15 minutes. The product on the glass plate carrier was cooled to 20°C. The product was placed in a 12% hydrochloric acid solution, ultrasonicated at 35kHz for 18 minutes, filtered and washed with anhydrous ethanol and pure water for 4 times each, and dried at -5°C and 5Pa for 7 hours to obtain helical carbon nanotubes. The helical carbon nanotubes and 45% nitric acid were mixed in a mass ratio of 1:9, and heated at 85°C and 900r / mi n stirred and reacted for 25 minutes, cooled to room temperature and filtered, washed with pure water 4 times, dried at -5°C, 5Pa for 7 hours, and obtained acid-treated spiral carbon nanotubes; the acid-treated spiral carbon nanotubes, thionyl chloride, and tetrahydrofuran were mixed uniformly in a mass ratio of 1:5:5, stirred and reacted at 45°C, 450min for 2.5 hours, heated to 65°C and continued to stir and react for 2.5 hours, filtered, and allowed to stand at 20°C, 1.5kPa for 5 hours, and then mixed uniformly with aminopropyltrimethoxysilane, triethylamine, and dichloromethane in a mass ratio of 3:2:0.8:22, stirred at 3°C, 400r / min for 55 minutes, allowed to stand at room temperature for 22 hours, filtered and washed with anhydrous ethanol 4 times, and dried at -5°C, 5Pa for 7 hours to obtain modified spiral carbon nanotubes; (2) 3-furoic acid, 2-mercaptobenzimidazole, anhydrous ethanol and pure water were mixed in a mass ratio of 1:1:5:5, and then 0.4 times the mass of neodymium chloride of 3-furoic acid was added, and the mixture was stirred at 35°C and 900 r / min for 4.5 h to obtain a fluorescent complex solution; styrene-butadiene-styrene block copolymer, ethyl diallyl silane and n-hexane were mixed in a mass ratio of 1:1:9, and then 0.04 times the mass of divinyltetramethyldisiloxane platinum salt of styrene-butadiene-styrene block copolymer was added, and the mixture was stirred and refluxed at 75°C and 650 r / min for 4 h, and then 1.4 times the mass of diethoxysilane of styrene-butadiene-styrene block copolymer was added, and the mixture was stirred and refluxed for 4 h, and then styrene-butadiene-styrene block copolymer was added. 1.4 times the amount of p-aminostyrene was added, and the mixture was stirred and refluxed for 4 hours, and allowed to stand at 25°C and 1.5 kPa for 3.5 hours, filtered and washed with pure water for 4 times, and dried at -5°C and 5 Pa for 7 hours to obtain a pre-modified styrene-butadiene-styrene block copolymer; the pre-modified styrene-butadiene-styrene block copolymer, the fluorescent complex solution, and n-hexane were mixed uniformly in a mass ratio of 1:6:4, and then 0.02 times the mass of the pre-modified styrene-butadiene-styrene block copolymer of carbodiimide was added, and the mixture was stirred and reacted at 25°C and 900 r / min for 2.5 hours, and allowed to stand at 35°C and 1.5 kPa for 9 hours, filtered and washed with pure water for 4 times, and dried at -5°C and 5 Pa for 7 hours to obtain a modified styrene-butadiene-styrene block copolymer; (3) The modified helical carbon nanotubes were placed in pure water for 2.5 min, and dried at -5°C and 5 Pa for 6 to 8 h to obtain pretreated modified helical carbon nanotubes; the pretreated modified helical carbon nanotubes, modified styrene-butadiene-styrene block copolymer, and polyethylene were uniformly mixed in a mass ratio of 1:1.5:2.5, and kneaded at 130°C for 25 min to prepare a sheath material with a thickness of 4 mm; the sheath material was wrapped on the optical cable core material, and rolled twice at 125°C and 9 MPa at 230 m / min to obtain a high elastic optical cable.
[0023] Example 3 A method for preparing a high elastic optical cable, the method for preparing the high elastic optical cable mainly comprises the following preparation steps: (1) Acetone, pyridine and acetylene were mixed in a mass ratio of 1:2:3 as a carbon source gas. A glass plate carrier evenly distributed with nano-iron oxide was placed in a reaction chamber in a nitrogen atmosphere. A carbon source gas 1200 times the mass of nano-iron oxide was introduced at a flow rate of 1000 sscm at 800°C, and then the ventilation was stopped for 10 minutes. Nitrogen was then introduced at the same flow rate for 20 minutes. The mixture was cooled to 30°C. The product on the glass plate carrier was placed in a 15% hydrochloric acid solution, ultrasonicated at 40kHz for 20 minutes, filtered and washed with anhydrous ethanol and pure water for 5 times each, and dried at -1°C, 10Pa for 8 hours to obtain helical carbon nanotubes. The helical carbon nanotubes and 50% nitric acid were mixed in a mass ratio of 1:10, and heated at 90°C, 1000 sscm. r / min stirring reaction for 20 minutes, cooling to room temperature and filtering, washing with pure water for 5 times, drying at -1°C, 10Pa for 8 hours, and obtaining acid-treated spiral carbon nanotubes; mixing the acid-treated spiral carbon nanotubes, thionyl chloride, and tetrahydrofuran in a mass ratio of 1:6:6, stirring and reacting at 50°C, 500r / min for 2 hours, heating to 670°C and continuing stirring and reacting for 3 hours, filtering, standing at 30°C, 2kPa for 6 hours, and then mixing with aminopropyltrimethoxysilane, triethylamine, and dichloromethane in a mass ratio of 3:3:1:25, stirring at 5°C, 500r / min for 50 minutes, standing at room temperature for 24 hours, filtering and washing with anhydrous ethanol for 5 times, and drying at -1°C, 10Pa for 6 hours, and obtaining modified spiral carbon nanotubes; (2) 3-furoic acid, 2-mercaptobenzimidazole, anhydrous ethanol and pure water were mixed in a mass ratio of 1:1:6:6, and then 0.5 times the mass of neodymium chloride of 3-furoic acid was added, and the mixture was stirred at 40°C and 1000 r / min for 4 hours to obtain a fluorescent complex solution; styrene-butadiene-styrene block copolymer, ethyl diallyl silane and n-hexane were mixed in a mass ratio of 1:1:10, and then 0.05 times the mass of divinyltetramethyldisiloxane platinum salt of styrene-butadiene-styrene block copolymer was added, and the mixture was stirred and refluxed at 80°C and 800 r / min for 5 hours, and 1.5 times the mass of diethoxysilane of styrene-butadiene-styrene block copolymer was added, and the mixture was stirred and refluxed for 5 hours, and then styrene-butadiene-styrene block copolymer was added. 1.5 times the mass of p-aminostyrene was continued, stirring and refluxing were continued for 5 hours, standing at 30°C, 2kPa for 4 hours, filtered and washed with pure water for 5 times, and dried at -1°C, 10Pa for 6 hours to obtain a pre-modified styrene-butadiene-styrene block copolymer; the pre-modified styrene-butadiene-styrene block copolymer, the fluorescent complex solution, and n-hexane were mixed uniformly at a mass ratio of 1:7:5, and then 0.03 times the mass of carbodiimide of the pre-modified styrene-butadiene-styrene block copolymer was added, stirred and reacted at 30°C, 1000r / min for 2 hours, standing at 40°C, 2kPa for 8 hours, filtered and washed with pure water for 5 times, and dried at -1°C, 10Pa for 6 hours to obtain a modified styrene-butadiene-styrene block copolymer; (3) The modified helical carbon nanotubes were placed in pure water for 3 minutes, and dried at -1°C and 10 Pa for 6 hours to obtain pretreated modified helical carbon nanotubes; the pretreated modified helical carbon nanotubes, modified styrene-butadiene-styrene block copolymer, and polyethylene were uniformly mixed in a mass ratio of 1:2:3, and kneaded at 140°C for 20 minutes to prepare a sheath material with a thickness of 4 mm; the sheath material was wrapped on the optical cable core material, and rolled twice at 130°C and 8 MPa at 240 m / min to obtain a high elastic optical cable.
[0024] Comparative Example 1 The preparation method of the high elastic optical cable of Comparative Example 1 is different from that of Example 2 only in step (1). Step (1) is modified as follows: the carbon nanotubes and 45% nitric acid are uniformly mixed in a mass ratio of 1:9, stirred at 85°C and 900 r / min for 25 min, filtered after cooling to room temperature, washed with pure water 4 times, and dried at -5°C and 5 Pa for 7 h to obtain acid-treated carbon nanotubes; the acid-treated carbon nanotubes, thionyl chloride and tetrahydrofuran are uniformly mixed in a mass ratio of 1:5:5, and heated at 4 5℃, 450min stirring reaction for 2.5h, heating to 65℃ and continuing stirring reaction for 2.5h, filtering, standing at 20℃, 1.5kPa for 5h, to obtain pre-modified carbon nanotubes; pre-modified carbon nanotubes, aminopropyltrimethoxysilane, triethylamine, dichloromethane were mixed uniformly in a mass ratio of 3:2:0.8:22, stirred at 3℃, 400r / min for 55min, standing at room temperature for 22h, filtering and washing with anhydrous ethanol 4 times, and dried at -5℃, 5Pa for 7h to obtain modified carbon nanotubes. The remaining steps were the same as in Example 2.
[0025] Comparative Example 2 The preparation method of the high elastic optical cable of Comparative Example 2 is different from that of Example 2 only in step (1). Step (1) is modified as follows: acetone, pyridine and acetylene are mixed uniformly in a mass ratio of 1:1:2 as a carbon source gas, a glass plate carrier uniformly distributed with nano-iron oxide is placed in a reaction chamber in a nitrogen atmosphere, and a carbon source gas 1100 times the mass of nano-iron oxide is introduced at a flow rate of 900 sscm at 750°C, then the ventilation is stopped for 7 minutes, and nitrogen is then introduced at the same flow rate for 15 minutes, cooled to 20°C, and the reaction mixture is stirred for 15 minutes. The product on the glass plate carrier was placed in a 12% hydrochloric acid solution, ultrasonicated at 35kHz for 18 minutes, filtered, washed with anhydrous ethanol and pure water 4 times each, and dried at -5°C, 5Pa for 7 hours to obtain a spiral carbon nanotube; the spiral carbon nanotube and 45% nitric acid were mixed uniformly at a mass ratio of 1:9, stirred at 85°C, 900r / min for 25 minutes, cooled to room temperature, filtered, washed with pure water 4 times, and dried at -5°C, 5Pa for 7 hours to obtain a modified spiral carbon nanotube. The remaining steps were the same as in Example 2.
[0026] Comparative Example 3 The preparation method of the high elastic optical cable of Comparative Example 3 is different from that of Example 2 only in step (2), and step (2) is modified as follows: 3-furoic acid, 2-mercaptobenzimidazole, anhydrous ethanol and pure water are mixed uniformly in a mass ratio of 1:1:5:5, and then 0.4 times the mass of neodymium chloride of 3-furoic acid is added, and stirred at 35°C, 900r / min for 4.5h to obtain a fluorescent complex solution; pre-modified styrene-butadiene-styrene block copolymer, fluorescent complex solution and n-hexane are mixed uniformly in a mass ratio of 1:6:4, and then 0.02 times the mass of carbodiimide of pre-modified styrene-butadiene-styrene block copolymer is added, and stirred at 25°C, 900r / min for 2.5h, and then allowed to stand at 35°C, 1.5kPa for 9h, filtered and washed with pure water for 4 times, and dried at -5°C, 5Pa for 7h to obtain a modified styrene-butadiene-styrene block copolymer. The remaining steps are the same as those of Example 2.
[0027] Comparative Example 4 The preparation method of the high elastic optical cable of Comparative Example 4 is different from that of Example 2 only in step (2), and step (2) is modified as follows: styrene-butadiene-styrene block copolymer, ethyl diallyl silane and n-hexane are mixed uniformly in a mass ratio of 1:1:9, and then 0.04% of the mass of the styrene-butadiene-styrene block copolymer of divinyltetramethyldisiloxane platinum salt is added, stirring and refluxing for 4 hours at 75°C and 650r / min, and 1.4 times of the mass of the styrene-butadiene-styrene block copolymer of diethoxysilane is added, and stirring and refluxing is continued for 4 hours, and 1.4 times of the mass of the styrene-butadiene-styrene block copolymer of p-aminostyrene is added, and stirring and refluxing is continued for 4 hours, and the mixture is allowed to stand at 25°C and 1.5kPa for 3.5 hours, filtered and washed with pure water for 4 times, and dried at -5°C and 5Pa for 7 hours to obtain a modified styrene-butadiene-styrene block copolymer. The remaining steps are the same as those of Example 2.
[0028] Comparative Example 5 A method for preparing a high elastic optical cable, the method for preparing the high elastic optical cable mainly comprises the following preparation steps: (1) Acetone, pyridine and acetylene were mixed in a mass ratio of 1:1:2 as a carbon source gas. A glass plate carrier evenly distributed with nano-iron oxide was placed in a reaction chamber in a nitrogen atmosphere. A carbon source gas 1100 times the mass of nano-iron oxide was introduced at a flow rate of 900 sscm at 750°C, and then the ventilation was stopped for 7 minutes. Nitrogen was then introduced at the same flow rate for 15 minutes. The product on the glass plate carrier was cooled to 20°C. The product was placed in a 12% hydrochloric acid solution, ultrasonicated at 35kHz for 18 minutes, filtered and washed with anhydrous ethanol and pure water for 4 times each, and dried at -5°C and 5Pa for 7 hours to obtain helical carbon nanotubes. The helical carbon nanotubes and 45% nitric acid were mixed in a mass ratio of 1:9, and heated at 85°C and 900r / mi n stirred and reacted for 25 minutes, cooled to room temperature and filtered, washed with pure water 4 times, dried at -5°C, 5Pa for 7 hours, and obtained acid-treated spiral carbon nanotubes; the acid-treated spiral carbon nanotubes, thionyl chloride, and tetrahydrofuran were mixed uniformly in a mass ratio of 1:5:5, stirred and reacted at 45°C, 450min for 2.5 hours, heated to 65°C and continued to stir and react for 2.5 hours, filtered, and allowed to stand at 20°C, 1.5kPa for 5 hours, and then mixed uniformly with aminopropyltrimethoxysilane, triethylamine, and dichloromethane in a mass ratio of 3:2:0.8:22, stirred at 3°C, 400r / min for 55 minutes, allowed to stand at room temperature for 22 hours, filtered and washed with anhydrous ethanol 4 times, and dried at -5°C, 5Pa for 7 hours to obtain modified spiral carbon nanotubes; (2) Styrene-butadiene-styrene block copolymer, ethyl diallyl silane and n-hexane were mixed in a mass ratio of 1:1:9, and then 0.04 mass of divinyltetramethyldisiloxane platinum salt of the mass of styrene-butadiene-styrene block copolymer was added, and the mixture was stirred and refluxed at 75°C and 650 r / min for 4 h. Diethoxysilane was added at a mass of 1.4 times that of the mass of the styrene-butadiene-styrene block copolymer, and the mixture was stirred and refluxed for 4 h. p-Aminostyrene was added at a mass of 1.4 times that of the mass of the styrene-butadiene-styrene block copolymer, and the mixture was stirred and refluxed for 4 h. The mixture was allowed to stand at 25°C and 1.5 kPa for 3.5 h. Filter and wash with pure water for 4 times, dry at -5°C, 5Pa for 7h to obtain pre-modified styrene-butadiene-styrene block copolymer; mix the pre-modified styrene-butadiene-styrene block copolymer, fluorescent complex solution and n-hexane in a mass ratio of 1:6:4, add 0.02 times the mass of the pre-modified styrene-butadiene-styrene block copolymer of carbodiimide, stir at 25°C, 900r / min for 2.5h, stand at 35°C, 1.5kPa for 9h, filter and wash with pure water for 4 times, dry at -5°C, 5Pa for 7h to obtain modified styrene-butadiene-styrene block copolymer; (3) 3-furoic acid, 2-mercaptobenzimidazole, anhydrous ethanol and pure water were mixed in a mass ratio of 1:1:5:5, and then 0.4 times the mass of neodymium chloride of 3-furoic acid was added, and the mixture was stirred at 35°C and 900 r / min for 4.5 h, and dried at -5°C and 5 Pa for 7 h to obtain a fluorescent complex; the modified helical carbon nanotubes were placed in pure water and allowed to stand for 2.5 min, and dried at -5°C and 5 Pa for 6-8 h to obtain pretreated modified helical carbon nanotubes; the pretreated modified helical carbon nanotubes, modified styrene-butadiene-styrene block copolymer, fluorescent complex and polyethylene were mixed in a mass ratio of 1:1.5:0.5:2.5, and kneaded at 130°C for 25 min to prepare a sheath material with a thickness of 4 mm, and the sheath material was wrapped on the optical cable core material, and rolled twice at 125°C and 9 MPa at 230 m / min to obtain a high elastic optical cable.
[0029] Effect example Table 1 below shows the performance analysis results of the tensile fracture resistance and anti-aging performance of the high elastic optical cables of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0030] Table 1 From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the high elasticity optical cable prepared in the present invention has good performance analysis results of tensile fracture resistance and anti-aging performance.
[0031] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1, it can be found that the performance retention rate of Examples 1, 2, 3 is higher than that of Comparative Example 1 under wet heat and temperature change conditions, which shows that the use of helical carbon nanotubes makes the helical carbon nanotubes have more contact with the remaining components of the overall material compared to the direct use of carbon nanotubes, and has a greater conduction effect on the thermal motion of molecules, thereby improving the anti-aging performance of the high elastic optical cable under wet heat and temperature change conditions; From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2, it can be found that the performance retention rate of Examples 1, 2, 3 is higher than that of Comparative Example 2 under wet heat and temperature change conditions. The high rate and high tensile strength indicate that the acid-treated helical carbon nanotubes are modified so that aminopropyltrimethoxysilane forms an amide bond connection with the helical carbon nanotubes, and the trimethoxysilane on the modified helical carbon nanotubes can be decomposed into silanol groups, which are cross-linked with each other to form a helical carbon nanotube thermal conductive network, thereby improving the overall cross-linking degree and the thermal conductive effect and thermal conductive stability, thereby improving the anti-aging performance and tensile fracture resistance of the high elastic optical cable under wet heat and temperature change conditions; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3, it can be found that Examples 1, 2, 3 are compared with Comparative Example 3 under temperature change and ultraviolet The performance retention rate under external conditions is high, which shows that after the styrene-butadiene-styrene block copolymer is pre-modified, the styrene-butadiene-styrene block copolymer has a longer silicone segment, and the silicone segment increases the stability of the styrene-butadiene-styrene block copolymer, reduces the impact of temperature changes on the overall performance, and cannot react with the subsequent fluorescent complex solution, thereby improving the anti-aging performance of the high elastic optical cable under temperature changes and ultraviolet conditions; by comparing the experimental data of Examples 1, 2, 3 and Comparative Example 4, it can be found that the performance of Examples 1, 2, 3 compared with Comparative Example 4 under ultraviolet and ozone conditions is better. The high retention rate indicates that after the pre-modified styrene-butadiene-styrene block copolymer is modified with the fluorescent complex solution, the fluorescent complex on the modified styrene-butadiene-styrene block copolymer can absorb strong light and ultraviolet rays and convert them into weak light and heat, reducing the damage of strong light and ultraviolet rays to the material. In an ozone environment, when the whole contains oxidizing substances, the benzimidazole on the fluorescent complex can respond in time, and the metal-sulfur coordination bond breaks to form benzimidazole containing sulfur free, which combines with oxidizing substances to reduce the oxidative decomposition of the main material, thereby improving the anti-aging performance of the high-elasticity optical cable under ultraviolet and ozone conditions;From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 5, it can be found that the performance retention rate of Examples 1, 2, 3 is higher than that of Comparative Example 5 under ultraviolet and ozone conditions, which shows that the fluorescent complex is grafted on the styrene-butadiene-styrene block copolymer. Compared with mixing and kneading, the amide bond on the modified styrene-butadiene-styrene block copolymer can form a hydrogen bond with the amide bond on the modified helical carbon nanotube, so that the fluorescent complex is close to the modified helical carbon nanotube, and the heat converted by ultraviolet absorption is transferred in time, and the fluorescent complex is protected to avoid loss, thereby improving the anti-aging performance of the high elastic optical cable under ultraviolet and ozone conditions. ;
[0032] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a highly elastic optical cable, characterized in that: The high elastic optical cable is made of a sheath material made of modified helical carbon nanotubes, modified styrene-butadiene-styrene block copolymer and polyethylene, and the sheath material is wrapped on the optical cable core material and rolled; The preparation method of the highly elastic optical cable mainly comprises the following preparation steps: (1) Acetone, pyridine and acetylene were mixed in a mass ratio of 1:1:2 as a carbon source gas. A glass plate carrier evenly distributed with nano-iron oxide was placed in a reaction chamber in a nitrogen atmosphere. A carbon source gas 1100 times the mass of nano-iron oxide was introduced at a flow rate of 900 sscm at 750°C, and then the ventilation was stopped for 7 minutes. Nitrogen was then introduced at the same flow rate for 15 minutes. The product on the glass plate carrier was cooled to 20°C. The product was placed in a 12% hydrochloric acid solution, ultrasonicated at 35kHz for 18 minutes, filtered and washed with anhydrous ethanol and pure water for 4 times each, and dried at -5°C and 5Pa for 7 hours to obtain helical carbon nanotubes. The helical carbon nanotubes and 45% nitric acid were mixed in a mass ratio of 1:9, and heated at 85°C and 900r / mi n stirred and reacted for 25 minutes, cooled to room temperature and filtered, washed with pure water 4 times, dried at -5°C, 5Pa for 7 hours, and obtained acid-treated spiral carbon nanotubes; the acid-treated spiral carbon nanotubes, thionyl chloride, and tetrahydrofuran were mixed uniformly in a mass ratio of 1:5:5, stirred and reacted at 45°C, 450min for 2.5 hours, heated to 65°C and continued to stir and react for 2.5 hours, filtered, and allowed to stand at 20°C, 1.5kPa for 5 hours, and then mixed uniformly with aminopropyltrimethoxysilane, triethylamine, and dichloromethane in a mass ratio of 3:2:0.8:22, stirred at 3°C, 400r / min for 55 minutes, allowed to stand at room temperature for 22 hours, filtered and washed with anhydrous ethanol 4 times, and dried at -5°C, 5Pa for 7 hours to obtain modified spiral carbon nanotubes; (2) 3-furoic acid, 2-mercaptobenzimidazole, anhydrous ethanol and pure water were mixed in a mass ratio of 1:1:5:5, and then 0.4 times the mass of neodymium chloride of 3-furoic acid was added, and the mixture was stirred at 35°C and 900 r / min for 4.5 h to obtain a fluorescent complex solution; styrene-butadiene-styrene block copolymer, ethyl diallyl silane and n-hexane were mixed in a mass ratio of 1:1:9, and then 0.04 times the mass of divinyltetramethyldisiloxane platinum salt of styrene-butadiene-styrene block copolymer was added, and the mixture was stirred and refluxed at 75°C and 650 r / min for 4 h, and then 1.4 times the mass of diethoxysilane of styrene-butadiene-styrene block copolymer was added, and the mixture was stirred and refluxed for 4 h, and then styrene-butadiene-styrene block copolymer was added. 1.4 times the amount of p-aminostyrene was added, and the mixture was stirred and refluxed for 4 hours, and allowed to stand at 25°C and 1.5 kPa for 3.5 hours, filtered and washed with pure water for 4 times, and dried at -5°C and 5 Pa for 7 hours to obtain a pre-modified styrene-butadiene-styrene block copolymer; the pre-modified styrene-butadiene-styrene block copolymer, the fluorescent complex solution, and n-hexane were mixed uniformly in a mass ratio of 1:6:4, and then 0.02 times the mass of the pre-modified styrene-butadiene-styrene block copolymer of carbodiimide was added, and the mixture was stirred and reacted at 25°C and 900 r / min for 2.5 hours, and allowed to stand at 35°C and 1.5 kPa for 9 hours, filtered and washed with pure water for 4 times, and dried at -5°C and 5 Pa for 7 hours to obtain a modified styrene-butadiene-styrene block copolymer; (3) placing the modified helical carbon nanotubes in pure water for 2.5 minutes, and drying them at -5°C and 5Pa for 6 to 8 hours to obtain pretreated modified helical carbon nanotubes; The pretreated modified helical carbon nanotubes, modified styrene-butadiene-styrene block copolymer and polyethylene were uniformly mixed in a mass ratio of 1:1.5:2.5, and kneaded at 130°C for 25 minutes to prepare a sheath material with a thickness of 4 mm. The sheath material was wrapped on the optical cable core material, and rolled twice at 125°C and 9 MPa at 230 m / min to obtain a high elastic optical cable.
Citation Information
Cited By
Protective coating for limiting rope in aviation oxygen supply mask pipeline and preparation method of protective coating
CN120005464A